Treatment with the GSK3‐beta inhibitor Tideglusib improves hippocampal development and memory performance in juvenile, but not adult, Cdkl5 knockout mice. (16th April 2018) - Fuchs, Claudia; Fustini, Norma; Trazzi, Stefania; Gennaccaro, Laura; Rimondini, Roberto; Ciani, Elisabetta
Abstract: Cyclin‐dependent kinase‐like 5 (CDKL5) disorder is a severe neurodevelopmental disorder characterized by early‐onset epileptic seizures, severe developmental delay, and intellectual disability. To date, no effective pharmacological treatments are available to improve the neurological phenotype that is due to mutations in the CDKL5 gene. Murine models of CDKL5 disorder have recently been generated, making the preclinical testing of pharmacological interventions possible. Using a Cdkl5 knockout (KO) mouse model, we recently demonstrated that deficiency of Cdkl5 causes defects in postnatal hippocampal development and hippocampus‐dependent learning and memory. These defects were accompanied by an increased activity of GSK3β, an important inhibitory regulator of many neuronal functions. Pharmacological inhibition of GSK3β activity was able to recover hippocampal defects and cognitive performance in juvenile Cdkl5 KO mice, suggesting that GSK3β inhibitors might be a potential therapeutic option for CDKL5 disorder. As GSK3β inhibitors have been shown to have differential medication responses in young people and adults, this study was designed to examine whether GSK3β is a possible therapeutic target both in juvenile and in adult CDKL5 patients. We found that treatment with the GSK3β inhibitor Tideglusib during the juvenile period improved hippocampal development and hippocampus‐dependent behaviors in Cdkl5 KO mice, while treatment later on in adulthood had no positive effects. These results suggest that pharmacological interventions aimed at normalizing impaired GSK3β activity might have different age‐dependent outcomes in CDKL5 disorder. This is of utmost importance in the development of therapeutic approaches in CDKL5 patients and in the design of rational clinical trials. Abstract : Pharmacological inhibition of GSK3 activity improves hippocampus development and function in a mouse model of CDKL5 disorder (the Cdkl5 knockout (KO) mouse) only when treatment is performed in an early time window of brain development, suggesting that a therapy with GSK3 inhibitors may be effective in CDKL5 patients only if administered early in postnatal development.